Gu lao de di yi : Xianggang guo ji shi ge zhi ye - Beidao, 1949-; Klein, Lucas; Song, Chris (The Chinese University Press, 2017)
International Poetry Nights in Hong Kong (IPNHK) is an award-winning biennial poetry festival established by the renowned contemporary Chinese poet Bei Dao. Since its debut in 2009, IPNHK has become the most influential series of international poetry events in sinophone areas, delivered internationally acclaimed poets' thoughts and ideas about poetry to contemporary China, and stimulated Chinese poets' reflection upon their own conditions of reading world poetry. Following the enormous success of previous editions, IPNHK's 2017 event is scheduled to happen from 22-26 November in Hong Kong, with the theme "Ancient Enmity," and invites more than twenty poets and lyricists from different parts of the world to share and read their works in the hope of encouraging exchange among poets and lyricists. Poets include Gabeba Baderoon (South Africa), Javier Bello (Chile), Chen Dongdong (China), Jérôme Game (France), Major Jackson (U.S.), George Szirtes (UK), Anja Utler (Germany), Haris Vlavianos (Greece), and others. The IPNHK anthology includes selections of the most internationally acclaimed contemporary poetry by the invited poets, accompanied by unique Chinese and English translations in bilingual or trilingual formats.